Infant-directed Speech by Dutch Fathers: Increased Pitch Variability within and across Utterances. Issue 3 (3rd July 2021) - Benders, Titia; StGeorge, Jennifer; Fletcher, Richard
ABSTRACT: Although both fathers and mothers speak differently in infant-directed speech (IDS) compared to adult-directed speech (ADS), the acoustic characteristics of present-day paternal IDS are still insufficiently understood. To extend this understanding, 11 fathers and 17 mothers in The Netherlands were recorded interacting with their infant (260–476 days old; for IDS) and with an adult experimenter (for ADS). Both fathers and mothers were found to raise their average pitch, expand their pitch variability within utterance, and increase their pitch variability across utterances in IDS. Moreover, fathers increased their pitch variability within and across utterances more than mothers. The IDS produced by present-day Dutch-speaking fathers is thus acoustically highly dynamic, in line with fathers' energetic interaction style.